Podcast como caminho de acesso: ferramenta tecnológica dando suporte à formação de uma comunidade educativamente mais crítica - Rosa, Ana Paula Paim da (2024)
The growing adherence and popularization of podcasts in Brazil encourages their use, still little explored scientifically, as a technology applied to education. In addition to understanding the Podcast as a tool that can be educational, it is remarkable its ability to be an easy, popular and accessible resource for the arrival of information to people. Therefore, I connect this issue with another relevant one, namely the importance of critical thinking. Starting from the union of these two themes, the present research arises, whose main objective is to map the limitations and potentialities of teacher training in the region of Santa María (RS) with respect to contemporary cross-cutting themes (TCTs) of BNCC, with the aim of building a podcast that takes a critical look at these issues. In addition, more specifically, the project will address: (1) identifying topics, understood within TCTs, that responding teachers have the greatest difficulty working; (2) analysing these particular topics plus a critical bias; (3) organize from the analysis of a product that addresses these problems with critical bias in a cooperative and popular way; and (4) need, after the organization of the product, the feasibility of working with TCTs from a critical bias. To achieve our objectives, we have adopted an applied methodological approach, with emphasis on exploration and qualitative research. Initially, we used a questionnaire as a tool to shape the practice of the podcast. Later, we applied another questionnaire with the same group of participants and anyone who wants to listen to an episode to evaluate and validate the relevance of the final product. Our theoretical framework is based on several sources, especially Brazil (2019) and Dos Santos (2022) that refer to TCTs; Cassany & Castellà (2010) and Beviláqua & Leffa (2020) that work critical reading; De Jesus (2014) and Freire (2017) that address the topic of the educational podcast. As a final result, we highlight that the Podcast has the potential to impact teachers, being considered by us as a kind of continuous training for teachers in TCTs with critical bias. In addition to the technological field, we consider that, when combined with the educational field, there was the promotion of a respectful collaboration between teachers of different areas, educational levels and with different experiences. Above all, our results can also be observed in the social field, since significant discussions were promoted for the continued emancipation of teachers, which can impact on the construction of a more critical society.